Students' Perspectives on Enhancing Vocabulary Through Song - Thalib, Rasuna; Mestari, Sri Agriyanti; Kau, Magvira El Walidayni; Paduay, Diofanny (Jurnal Bahasa, Sastra, dan Budaya, 2024)
The purpose of this study is to investigate junior high schoolstudents' perspectives regarding the efficacy of teaching vocabulary inEnglish through the use of English songs. The participants in this studywere 9th-grade students of SMP Negeri 1 Kabila Bone in the academicyear 2023-2024. This is a qualitative study which use interview in openendedquestions form in gathering the data. The result showed thatsongs provide a dynamic and engaging approach which may capturingstudents and minimizing monotony in the classroom. Students' interestalso was sparked by the rhythmic beat and fun of the songs, whichencouraged active involvement and made learning vocabularyenjoyable. Songs also helped students expand and acquire theirvocabulary by giving them context-rich examples of word usage andenhancing their language comprehension. In summary, the use of songsin vocabulary learning creates an engaging, enjoyable, and effectiveeducational experience.